Palaeomagnetic Study of Tectonic Rotations in the Eastern Betic Cordillera, Southern Spain. - Mc Clelland, E.; Platt, J.P.; Platzman, E.S.; Allerton, S.; Lonergan, L. (Física de la Tierra, 1992)
Sin resumen